2015
DOI: 10.4238/2015.august.10.11
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of the BoTFL1-like gene of Bambusa oldhamii delays blossoming in Arabidopsis thaliana and rescues the tfl1 mutant phenotype

Abstract: ABSTRACT. TERMINAL FLOWER1 (TFL1) homologous genes play major roles in maintaining vegetative growth and inflorescence meristem characteristics in various plant species; however, to date, the function of the bamboo TFL1 homologous gene has not been described. In this study, a TFL1 homologous gene was isolated from Bambusa oldhamii and designated as BoTFL1-like. Phylogenetic analysis of TFL1 homologous genes revealed that BoTFL1-like shared more than 90% identity with the TFL1 genes of other Gramineae. RT-PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
1
8
0
1
Order By: Relevance
“…Our BLAST analyses identified five copies of Ph.TFL1 genes in P. heterocycla (Table 1). A functional TFL1 gene was isolated from B. oldhamii and was overexpressed in Arabidopsis (Zeng et al, 2015). The overexpressed lines showed delayed flowering, suggesting that TFL1 may have a role in maintaining vegetative growth.…”
Section: Possible Physiological and Genetic Factors Regulating Bamboomentioning
confidence: 99%
See 1 more Smart Citation
“…Our BLAST analyses identified five copies of Ph.TFL1 genes in P. heterocycla (Table 1). A functional TFL1 gene was isolated from B. oldhamii and was overexpressed in Arabidopsis (Zeng et al, 2015). The overexpressed lines showed delayed flowering, suggesting that TFL1 may have a role in maintaining vegetative growth.…”
Section: Possible Physiological and Genetic Factors Regulating Bamboomentioning
confidence: 99%
“…In comparison, the molecular aspects of bamboo flowering remain at a nascent stage. Studies have been conducted to characterize a limited number of flowering genes in different bamboo species such as MADS18 from Dendrocalamus latiflorus (Bo et al, 2005), FLOWERING LOCUS T (FT) from P. meyeri (Hisamoto et al, 2008), TERMINAL FLOWER 1 (TFL1) like gene from Bambusa oldhamii (Zeng et al, 2015), FRIGIDA (FRI) from P. violascens (Liu et al, 2015), MADS1 and MADS2 from P. praecox (Lin et al, 2009), 10 genes related to floral transition and meristem identity in D. latiflorus (Wang et al, 2014) and 16 MADS box genes from B. edulis (Shih et al, 2014). Such targeted approaches are being complemented by high-throughput approaches, namely, de novo transcriptome sequencing and suppression subtractive hybridization (Lin et al, 2010; Liu et al, 2012; Zhang et al, 2012; Peng et al, 2013; Gao et al, 2014; Ge et al, 2016; Wysocki et al, 2016; Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some species have a lengthy vegetative stage that may last more than 120 years while other species flower after only 1 year. Little is known about floral induction in bamboo or the genes involved in the process [ 6 , 15 17 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many flowering promoters in bamboo have been reported ( Tian et al, 2005 ; Lin et al, 2009 , 2010 ; Guo et al, 2016 ; Liu et al, 2016a ). We previously showed that BoTFL1-like and PvFRIL might be possible floral suppressors of bamboo ( Zeng et al, 2015 ; Liu et al, 2016c ). In this study, we identified and characterized another possible floral suppressor, a Pin1-like gene from P. violascens named PvPin1.…”
Section: Discussionmentioning
confidence: 99%